Evaluation of ULF activity on the electron transportation in the outer radiation belt - José Paulo Marchezi (2020)
Van Allens radiation belts consist of two regions with entrapment of charged particles in the Earths magnetic field: inner and outer belts. The inner belt is composed mainly of protons with energies between 100 keV and a few hundred MeV. The outer belt is primarily consisting of high-energy electrons, ranging from dozens of keV to a few dozen MeV. Those particles rotate around the field line, mirroring movement along the magnetic field line and a drift movement around the Earth. Each movement has a particular time and is associated with an adiabatic invariant. Changes in the configuration of the solar magnetic field influence the solar wind and, consequently, all planets and spaceships within the heliosphere can be affected by disturbances of the solar wind. Interplanetary Coronal Mass Ejections (ICME) and fast solar wind High-Speed Streams (HSS), cause disturbances in the Earths magnetosphere, including radiation belts from Van Allen. ICME events are more frequent during the growing phase of the solar cycle, while HSS is more critical during the declining period. The characteristics of the disturbances observed in the flux of electrons from the outer radiation belt due to these events are also different. Since October 2012, NASA initiated the Van Allen Probes mission that monitors, among other parameters, the magnetic field and the variation of particles in the radiation belts. The main objective of this work is to describe, based on observational data, the radial diffusion mechanism in the presence of ULF waves. For this, it is necessary to explain the role of ULF waves in the frequency bands corresponding to the natural oscillations of the magnetosphere, that is, Pc4 and Pc5, observed in the region of the external radiation belt, during periods of increased relativistic electron flux in the outer radiation belt. The energy penetration capacity as a function of the L-shell of the magnetosphere was investigated for the different frequency ranges considered in this research. The radiation belt events were investigated when related to HSS and ICME occurrences. Statistical results considering all ICMEs and HSS during the Van Allen Probes era show that for both solar wind structures, solar wind plasma parameters are strongly related to the radiation belt response at L − shell = 5 RE, and on average they show a higher magnitude compared to those related to decrease in particle flux. Also, the ULF wave power is obtained as being more intense throughout enhancement events. Finally, we compare the integrated ULF wave power measured by the satellites and obtained via empirical modeling, for each L-shell, the results show that the empirical model overestimates integrated power for all the investigated L-shells and it discrepancy is increased at higher L-shells.